The Analysis of Implementation Halal Certification for Micro, Small, And Medium Enterprises (MSMES) In Padangsidimpuan City - Nikma Sari Harahap; Rozalinda Rozalinda; Nora Zulvianti (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
This study aims to analyse the implementation of halal certification for Micro, Small, and Medium Enterprises (MSMEs) in Padangsidimpuan City, focusing on the impacts, challenges, and government support in the certification process. Halal certification has excellent potential to increase the competitiveness of MSMEs in the domestic and international markets, considering that most of the residents of Padangsidimpuan City are Muslims. The results of the study show that halal certification has a positive impact on increasing sales, consumer confidence, and market expansion. However, MSMEs face several significant obstacles, such as high certification costs, the complexity of procedures, and the need to understand the importance of halal certification. Through training, socialisation, and subsidies for certification fees, government support has made a positive contribution but still needs improvement. This research provides policy recommendations to overcome these obstacles, including increasing subsidies, digitising the certification process, and public awareness campaigns about the importance of halal products. Overall, this study reveals halal certificationâ€™s great potential in encouraging halal-based MSMEsâ€™ growth in Padangsidimpuan City. Still, a better-supporting mechanism is required so that more MSMEs can exploit halal market opportunities.Â